2017
DOI: 10.1902/jop.2016.160396
|View full text |Cite
|
Sign up to set email alerts
|

The Proteasome Inhibitor Bortezomib Inhibits Inflammatory Response of Periodontal Ligament Cells and Ameliorates Experimental Periodontitis in Rats

Abstract: These findings demonstrate the anti-inflammatory activity of BTZ against periodontal inflammatory response and present BTZ as a promising therapy for periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
1
13
0
1
Order By: Relevance
“…Other relevant factors are porosity, fiber size, individual fiber orientation in the mesh, entanglements of the fiber, and so on. It has been reported that HA nano-particle incorporation within the PHB fibers significantly improved the mechanical properties of PHB mats with an increase of 67% of the elastic modulus and 51% of the tensile strength at break [20]. In this study, we found chitosan nano-particles adhesive bonding to the junction of the PLA fibers.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Other relevant factors are porosity, fiber size, individual fiber orientation in the mesh, entanglements of the fiber, and so on. It has been reported that HA nano-particle incorporation within the PHB fibers significantly improved the mechanical properties of PHB mats with an increase of 67% of the elastic modulus and 51% of the tensile strength at break [20]. In this study, we found chitosan nano-particles adhesive bonding to the junction of the PLA fibers.…”
Section: Discussionsupporting
confidence: 63%
“…The tensile deformation of nanofibers is strongly dependent on the level of the nano-fibers alignment within the mat, interface adhesion of fiber-fiber contact and fiber lay-ups [18,19]. Usually, the modulus and tensile strength of the mats with uniaxially oriented fibers are higher than that of the non-woven fiber mat [20]. Other relevant factors are porosity, fiber size, individual fiber orientation in the mesh, entanglements of the fiber, and so on.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that bortezomib inhibits the expression of IL-1β and prevents alveolar bone absorption in experimental periodontitis. 166 CONCLUSION IL-1β is an important pro-inflammatory cytokine and participates in periodontitis. As a strong stimulator of bone resorption, continuous bone loss may be induced by IL-1β.…”
Section: Other Potential Agents That Influence Il-1β In Periodontitismentioning
confidence: 99%
“…Bone remodeling requires a precise balance between bone formation and resorption (Sato et al, 2016). It is well-known that RANKL is a cytokine which can induce the differentiation of progenitor cells into mature osteoclast (Jiang et al, 2016). Conversely, OPG is an osteoprotegerin which can block the binding of a RANK ligand (RANKL) to the RANK receptor (Kurinami et al, 2016).…”
Section: Discussionmentioning
confidence: 99%